2020
DOI: 10.1038/s41598-020-59257-z
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to decompose motion data into task-relevant and task-irrelevant components in categorical outcome

Abstract: In this paper, we propose a data-driven technique to detect task-relevant and task-irrelevant motion components with categorical task outcomes. Our method relies on a linear regression technique for solving classification problems, such as logistic regression 7. For example, logistic regression enables classification of whether the current motion data are associated with throwing a fastball or breaking ball. Our data-driven method can be applied even when the relation between motion data and outcome is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Another perspective on the redundancy problem is the decomposition of motion data into task-relevant and task-irrelevant components 28 , 29 and the suppression of motor variability, especially in task-relevant motion components 29 . To discuss task-relevant and task-irrelevant features, different types of data-driven methods 30 32 are preferable rather than tensor decomposition. Because the current study focused on the effort-dependent effects on multiple and time-varying muscle activities, we relied on tensor decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Another perspective on the redundancy problem is the decomposition of motion data into task-relevant and task-irrelevant components 28 , 29 and the suppression of motor variability, especially in task-relevant motion components 29 . To discuss task-relevant and task-irrelevant features, different types of data-driven methods 30 32 are preferable rather than tensor decomposition. Because the current study focused on the effort-dependent effects on multiple and time-varying muscle activities, we relied on tensor decomposition.…”
Section: Discussionmentioning
confidence: 99%
“….,K). To estimate the relevance, our earlier studies demonstrated the effectiveness of a ridge regression rather than some nonlinear regression techniques [10,23,24]. A ridge regression allows us to estimate the relevance of motion to performance data W2R [I, J] while minimizing prediction error in the presence of observation noise (see Methods for details).…”
Section: Detection Of Task-relevant Spatial and Temporal Modulesmentioning
confidence: 99%
“…A comparison of motion-relevant and task-relevant modules provides insight into the relationship between motion-relevant modules and task-relevant components. First, our framework is based on ridge regression [22] to predict task performance based on time-varying multidimensional motion data [10,23,24]. A ridge regression allows us to quantify how motion data in each time frame in each body part are relevant to predicting task performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus evaluated the motion components relevant to the classification of tempo into its fastest and natural components while expecting to quantify the effects of skill learning on feedforward control. To extract the nontrivial classification-relevant motion components, we utilized a data-driven technique (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%